Tunable gold nanorod/NAO conjugates for selective drug delivery in mitochondria-targeted cancer therapy. Issue 22 (26th May 2022) - González-Rubio, Sergio; Salgado, Cástor; Manzaneda-González, Vanesa; Muñoz-Úbeda, Mónica; Ahijado-Guzmán, Rubén; Natale, Paolo; Almendro-Vedia, Víctor G.; Junquera, Elena; Barcina, José Osío; Ferrer, Irene; Guerrero-Martínez, Andrés; Paz-Ares, Luis; et al.
Abstract : Nano-conjugates composed of gold nanorods and nonyl acridine orange (NAO) derivatives were built as a novel approach for mitochondria targeted-cancer therapy. Abstract : Nonyl acridine orange (NAO) is a lipophilic and positively charged molecule widely used as a mitochondrial fluorescent probe. NAO is cytotoxic at micromolar concentration and might be potentially used as a mitochondria-targeted drug for cancer therapy. However, the use of NAO under in vivo conditions would be compromised by the unspecific interactions with off-target cells and negatively charged proteins present in the bloodstream. To tackle this limitation, we have synthesized NAO analogues carrying an imidazole group for their specific binding to nitrilotriacetic (NTA) functionalized gold nanorods (AuNRs). We demonstrate that AuNRs provide 10 4 binding sites and a controlled delivery under acidic conditions. Upon incubation with mouse embryonic fibroblasts, the endosomal acidic environment releases the NAO analogues from AuNRs, as visualized through the staining of the mitochondrial network. The addition of the monoclonal antibody Cetuximab to the conjugates enhanced their uptake within lung cancer cells and the conjugates were cytotoxic at subnanomolar concentrations ( c 50 ≈ 0.06 nM). Moreover, the specific interactions of Cetuximab with the epidermal growth factor receptor (EGFR) provided a specific targeting of EGFR-expressing lung cancer cells. After intravenous administration in patient-derived xenografts (PDX) mouse models, the conjugates reduced the progression of EGFR-positive tumors. Overall, the NAO-AuNRs provide a promising strategy to realize membrane mitochondria-targeted conjugates for lung cancer therapy.